STUDENTS' SWIMMING COMPETENCIES: THE ROLE OF THE SCHOOL PHYSICAL EDUCATION - Tatjana Vlahović (Exercise and Quality of Life)
Physical education has an important role in students' preparation for lifelong fitnessparticipation. Since swimming is considered as one of the most beneficial fitness activities,swimming competencies, including knowledge of safety routines, should be developedthrough physical education classes. In order to examine swimming competencies ofelementary and secondary school students, the cross-sectional study was conducted. Thesample consisted of 143 students of both gender (71 elementary school students, 72 secondaryschool students). The previously used questionnaire was modified (Moran, 2006) and the dataconcerning selfevaluation of swimming skills, safety information resources and life savingskills are presented. Data were analyzed by descriptive statistics. Results suggest that there areno significant differences between elementary and secondary school students inselfevaluations of swimming skills, but they differ in safety information resources they use.Schools fail in their mission to educate and develop students' swimming competencies.